Intrinsic Elements and Sociological Criticism of Green Book Movie - Rani, K Dian; Winaya, I Made (Humanis, 2020)
The aims of the study were to find out the content of intrinsic elements of the Green Book movie and criticize the movie from sociological perspective. The study used qualitative method. It applied the theory of literature specfically intrinsic elements of drama proposed by Diniejko (2010) and sociological criticism proposed by Rapaport (2011). The results of the study were , firstly, the intrinsic elements found in the Green Book movie are plots, character, dialogue, setting, conflict, theme and motif which support the deeper understanding of the internal part of the movie. Secondly, by conducting a sociological criticism, it is found that the movie is related to the social condition of America in 1962 and it has correlation with the situation faced by American white and black nowadays.